Hubungan Antara Perilaku Kepemimpinan Kepala Sekolah dan Disiplin dengan Motivasi Kerja Guru pada SMP di Pulau Buana - Sahama Nanilette; Izaak Hendrik Wenno; Sumarni Rumfot (LP. Ma'arif Janggan Magetan, 2023)
This study aims to determine the relationship between the behavioral orientation of school principals and discipline leadership with the work motivation of teachers in junior high schools on the island of Buano. The research method used in this research is quantitative research. From this data it can be concluded that: 1) There is a relationship between the leadership behavior of school principals and teachers' work motivation because the significant value is < 0.05 or 0.150 < 0.05. The value of the Pearson correlation is 0.912, which means that there is a degree of relationship at very low correlation. 2) There is a relationship between work discipline and teacher motivation because the significant value is <0.05 or 0.00 <0.05. The value of the Pearson correlation is 0.873, which means that there is a high degree of correlation. 3) There is a positive and significant relationship between the principal's leadership behavior and work discipline with the teacher's work motivation because the significant value is <0.05. Thus it can be concluded that there is a positive and significant relationship simultaneously between the leadership behavior of school principals and work discipline with teacher work motivation. so it can be concluded that H0 is rejected and H1 is accepted.